1999
DOI: 10.1515/zna-1999-0208
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Spectra of Phosphorus Monosulfide up to 1 THz

Abstract: The submillimeter-wave rotational spectrum of the PS radical in the electronic and vibrational ground state (A' 2 77I/ 2 , X 2 IJ 3 / 2 ) was recorded with the Cologne terahertz spectrometer in the frequency region between 540 GHz and 1.07 THz, covering rotational quantum numbers from J = 30.5 to 60.5. The PS radical has been produced by discharging PSC1 3 buffered with Ar. For all transitions the yl-doubling was resolved for both the 2 77I/2 and 2 77 3 / 2 states. For some transitions with AF = 0 the hyperfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…These conditions are rather different from those found to produce high yields of PH (9). High H 2 partial pressures increased the PH 2 yields, but were also found to broaden the lines.…”
Section: Methodscontrasting
confidence: 60%
See 1 more Smart Citation
“…These conditions are rather different from those found to produce high yields of PH (9). High H 2 partial pressures increased the PH 2 yields, but were also found to broaden the lines.…”
Section: Methodscontrasting
confidence: 60%
“…The present investigation of PH 2 follows the laboratory studies of the phosphorus-containing molecules PH (8), PS (9), and CP (10). Since the first observation of the electronic spectrum of PH 2 in the gas phase in 1956 (11), numerous studies of this radical have appeared in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…Simultaneously, Ohishi et al [51] observed the microwave spectrum of PS and determined the groundstate molecular constants from the analysis of the infrared [50] and microwave data. Through analysis of the observed rotational spectra of PS up to 1 THz, Klein et al [52] determined the rotational, -doubling, and hyperfine parameters.…”
Section: Resultsmentioning
confidence: 99%
“…PS was observed in the laboratory for the first time by Dressler & Miescher (1955) who detected two band systems corresponding to the C 2 Σ → X 2 Π and B 2 Π → X 2 Π electronic transitions, with wavelength ranges 2700-3100 Å and 4200-6000 Å respectively. Since then a limited set of experiments on PS have followed (Narasimham & Subramanian 1969;Narasimham & Balasubramanian 1971;Jenouvrier & Pascat 1978;Balasubramanian et al 1979;Lin et al 1987;Kawaguchi et al 1988;Ohishi et al 1988;Wang et al 1993) with the most recent being the study of a submillimeter-wave rotational spectrum by Klein et al (1999). Several of these studies are considered further below.…”
Section: Introductionmentioning
confidence: 99%